2005
DOI: 10.1203/01.pdr.0000188698.58021.ff
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Maternal Diabetes on Vascular Reactivity and Renal Function in Rat Male Offspring

Abstract: Fetal growth impairment can occur in pregnancy complicated by diabetes. Although several studies have focused the effects of nutritional status on intrauterine development, the long-term impact of maternal diabetes on vascular and renal function in the offspring is poorly investigated. In the present study, blood pressure profiles and renal function parameters were investigated in the offspring of diabetic rats (DO). Female rats were made diabetic throughout gestation with a single dose of streptozotocyn (STZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
92
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 41 publications
4
92
1
1
Order By: Relevance
“…Interestingly, in inbred rat models of hypertension, the relationship between nephron number and blood pressure is still a matter of debate (24 -26). In addition, recently, Rocha et al (8) and Magaton et al (9) reported hypertension in rats issued from diabetic mothers without inborn nephron deficit. However, their model slightly differs from ours: 1) The level of maternal hyperglycemia is more pronounced in our model (we have previously shown that inborn nephron deficit correlated with the level of maternal hyperglycemia [13]); and 2) we performed direct glomerular counting with the gold-standard acid-maceration method, whereas they used an histological-derived method that is more appropriate to evaluate the density of glomeruli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in inbred rat models of hypertension, the relationship between nephron number and blood pressure is still a matter of debate (24 -26). In addition, recently, Rocha et al (8) and Magaton et al (9) reported hypertension in rats issued from diabetic mothers without inborn nephron deficit. However, their model slightly differs from ours: 1) The level of maternal hyperglycemia is more pronounced in our model (we have previously shown that inborn nephron deficit correlated with the level of maternal hyperglycemia [13]); and 2) we performed direct glomerular counting with the gold-standard acid-maceration method, whereas they used an histological-derived method that is more appropriate to evaluate the density of glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these two sets of results seem to weight against a compensatory glomerular hypertrophy and hyperfiltration as factors of alteration and worsening of the renal function until 18 months of age. Concerning the study of Rocha et al (8), one must note that although decreased nephron number was not observed in young animals, the number of nephrons was reduced at 12 months in diabetic mother offspring rats. However, because no histological data were provided in their study to evaluate the extent of glomerulosclerosis, the mechanisms of ongoing nephron loss and its implication in the decline of renal function has not been elucidated in their model.…”
Section: Figmentioning
confidence: 93%
See 1 more Smart Citation
“…In a previous study, we have demonstrated that maternal diabetes promotes remarkable changes in both kidney function and vascular reactivity in the mature offspring (15). Our data concerning diabetic offspring model (DO) pointed to an interesting model in which, although a normal nephron number was observed, two important factors-systemic hypertension and glomerular hypertrophy-which contribute to the progression of renal disease, were present.…”
mentioning
confidence: 62%
“…No alteration in nephron number and in renal morphology was observed in the young offspring (15,29). In the study from Magaton et al (29), immunohistochemical analysis for antiproliferating cell nuclear antigen (PCNA), an index of growth rate, and for ␣-SM-actin, overexpressed during pathologic states, showed a similar pattern in both C and DO groups; these results confirm previous data from our group which indicate no renal morphologic changes in the young and adult offspring from diabetic mothers (15).…”
Section: Discussionmentioning
confidence: 83%